Consequences of Emergence Timing for the Growth and Relative Survival of Steelhead Fry from Naturally Spawning Wild and Hatchery Parents. Issue 5 (12th August 2015) - Jones, Marissa H.; Seeb, James E.; Warheit, Kenneth I.; Seamons, Todd R.; Quinn, Thomas P.; Seeb, Lisa W.
Abstract: For many fishes, reproducing early in the year may present tradeoffs for the offspring: the drawbacks associated with harsh environmental conditions may be offset by advantages in competition for food and space. We investigated this tradeoff in a system where hatchery‐origin steelhead Oncorhynchus mykiss were bred to spawn about 4 months earlier than wild‐origin fish. Hatchery‐origin adults were released into the wild and spawned in common with wild steelhead. Naturally spawned offspring from these matings were assigned to hatchery, wild, and hybrid lineages by using a panel of 96 single‐nucleotide polymorphisms. We then evaluated whether fry abundance, body size and condition, and geographic distribution differed based on parental lineage. The observed mixture proportions were 0.007 hatchery‐lineage, 0.289 hybrid, and 0.704 wild‐lineage juveniles, despite the predominance of hatchery‐origin parents. There were significant differences in FL (hatchery > hybrid > wild) but no difference in body condition. We modeled the emergence dates of the sampled fry and estimated that 96.0% of wild‐lineage fish emerged after the arrival of temperate spring conditions (reduced flows and warmer temperatures) compared with 80.4% of hybrids and 41.2% of hatchery‐lineage fish. We hypothesize that the low abundance of pure hatchery‐lineage fry may be due to a mismatch between the timing of breeding by the parents and suitable river conditions, resulting in low survival and physical displacement of hatchery‐lineage fry from the system. Thus, the advantages of early emergence and large size associated with hatchery origin did not mitigate the disadvantages of early spawning in this case.